PENYULUHAN DAN PELATIHAN FISIOTERAPI PADA LANSIA DI POSYANDU HANDAYANI PUSKESMAS TONDANO KECAMATAN PEKALONGAN TIMUR KOTA PEKALONGAN Tema: Latihan Keseimbangan, Pernafasan untuk Meningkatkan Aktivitas Fungsional pada Lansia - Ade Irma Nahdliyyah; Nur Achiri M; Tiara Arifandi (LPPM Universitas Pekalongan, 2020)
Counseling and Physiotherapy Training with Balance, Respiratory Exercise to Improve Functional Activities in the Elderly in Posyandu Handayani Tondano Health Center in East Pekalongan District Pekalongan City was attended by posyandu cadres, physiotherapists, and the main target is the elderly Posyandu Handayani in Puskermas Tondano Timur Pekalongan District Pekalongan City was attended by posyandu cadres, physiotherapists, and the main target is the elderly Posyandu Handayani in Puskermas Tondano Timur Pekalongan District Pekalongan City. Posyandu Handayani consists of 7 posts, each post consists of approximately 70 elderly with an age range of 50 years and over. Most of the elderly posyandu handayani members are women, half of them are still productive and others are not able to perform functional activities to the full. The majority of posyandu handayani members come from the lower middle class with low education levels. From the observation of the identification of physiotherapy problems in the elderly carried out by 6th semester students and lecturers of Study Program D III Physiotherapy, Faculty of Health, Pekalongan University, it was found that the elderly at Posyandu Handayani in Puskermas Tondano with poor balance conditions, when walking away the elderly experience their breathing wheezing. and the daily activities of the elderly tend to make the wrong moves. The solution offered to solve the problem is to use a situation analysis method in the form of observation with a physiotherapy assessment method. Participants who attended counseling and training as many as 40 people, 20 of whom experienced impaired balance and breathing. From the results of the pre-test and post conducted before and after counseling and training there are significant results about the knowledge of the elderly will increase functional activity with breathing and balance training methods.Keywords: Elderly, balance training, breathing exercises, functional activities